Determinants of Refugee Children’s Self-Perceived Educational Performance: A Comparative Study of Lebanon, Turkey, and Australia - Maha Shuayb; Mohammad Hammoud (Social Sciences)
This study investigates how differing educational frameworks across Lebanon, Turkey, and Australia influence the perceived educational performance of Syrian refugee children. The legal status granted to refugees in each country fundamentally shapes their respective education systems’ responses. In Lebanon, refugees are generally classified as temporarily displaced persons, resulting in an emergency-based approach to education for the approximately 500,000 Syrian children present. By contrast, Australia has offered permanent resettlement opportunities to selected Syrian refugees, integrating them directly into mainstream schools. Turkey, meanwhile, has progressively shifted from emergency-based measures to policies oriented toward long-term integration. This research is based on survey data from 1298 Syrian refugee children across the three contexts. Findings from ordered probit regression analyses indicate that, beyond the legal duration of residency and the prevailing educational policy model (emergency versus long-term integration), variables such as the extent of educational segregation, the availability of preparatory and language support programmes, and the socioeconomic status of families are also pivotal in shaping students’ self-perceived academic performance.